Electrodeposited Fe2TiO5 nanostructures for photoelectrochemical oxidation of water. (20th September 2016) - Lin, Yan-Gu; Hsu, Yu-Kuei; Lin, Yu-Chang; Chen, Ying-Chu
Abstract: Electrodeposition was used to fabricate nanostructured films of Ti-containing hematite for application to the photoelectrochemical (PEC) splitting of water. The morphology and microstructure of Ti-doped hematite were examined with a scanning electron microscope, X-ray diffraction, Raman spectra and X-ray photoelectron spectra. Optical absorption spectra indicated an enhanced light absorbance in Ti-doped hematite. This Ti doping increased the carrier concentration about ten-fold, confirmed with a Mott-Schottky analysis. The prepared Ti-doped hematite showed a photocurrent enhanced four-fold relative to pristine hematite. Synchrotron-based soft X-ray absorption spectra clearly revealed that a local Fe2 TiO5 structure in hematite formed a heterojunction, which decreased the accumulation of photogenerated holes and improved the performance.